Современное состояние популяции корсака (Vulpes corsac L.) на Украине - Волох, Анатолий Михайлович; Волох, Анатолій Михайлович; Volokh, Anatolii (Российский ГАЗУ, 2013)
RU: Приводятся сведения о распространении корсака на Украине, популяция которого сформировалась в конце ХХ в. Сообщаются случаи отдельных заходов этого зверька и анализируются причины, способствующие возникновению постоянных очагов обитания степного вида в стране. EN: Earlier, the corsac was a common species in the South East Ukraine, where its principal areas of residence were virgin steppes. Now they are plowed and turned into fields that are subject to intense influence of agricultural industry which entailed disappearance of the corsac from Ukrainian fauna in 1950s. However, in 1973 some individuals began penetrating in the north-eastern Lugansk and Donetsk regions where steppe sites still preserved. Currently, in Streltsovskaya and Provalskaya steppes a small population of сorsacs has been formed, and it included in the Red Data Book of Ukraine (2009). The current penetration of the predator in Ukraine most likely is a consequence of the natural pulsation of the corsac range, caused by global warming that reduced mortality of dispersing animals in winter. Certain value for its successful distribution had also the decline of anthropogenic pressure on the environment due to the drop in agricultural production after the collapse of the Soviet Union. Among other positive factors it should be mentioned a significant reduction in hunting pressure on populations of fur-bearing animals as a result of cheap local furs and appreciation of hunting licenses, as well as increase in the size of protected ar-eas.
Current status of population corsak (vulpes corsac l.) in Ukraine
Keywords: ареал; биотопы; корсак